The behaviour of PT-based alloys at high temperature - Tshawe, Wendy (My University, 2009)
Previously published work on the development of the Pt-based superalloys for high temperature and special applications, as well as phase equilibria work, showed that there were problems and uncertainties with the available Pt-Al phase diagram. The aim of the current work was to make a comprehensive study of all relevant phases, and to clarify the phase boundaries of the phases: (Pt), Pt3Al (all temperature versions), Pt2Al (both phases), and Pt5Al3, by use of higher resolution SEM and XRD. A displacive transformation was confirmed for cubic Pt3Al to tetragonal Pt3Al and from high temperature Pt2Al to low temperature Pt2Al. The -phase was observed to be present, the phase reactions were confirmed and the eutectic composition was found. The Pt6Al21 phase was identified instead of Pt5Al21, and was deduced to be a different interpretation of the same phase, although the former had been described as a metastable phase. The phases and phase boundaries were found to generally agree with Massalski, and disagreed with Oya et al. ’s phase diagram
Keywords: Pt-based alloys; Aluminium; Pt platinum; Phase diagrams